L’archéologie du groupe épiscopal d’Elne (Pyrénées-Orientales) de l’Antiquité tardive à l’époque moderne - Olivier Passarrius; Jérôme Bénézet; Aymat Catafau; Camille Mistretta Verfaillie; Michel Martzluff; Sylvain Lambert (Archéologie Médiévale)
In 2017, the foundations of a large church were unearthed on the plateau des Garaffes in Elne (Pyrénées-Orientales – France), 20 m east of the Romanesque cathedral built from the 11th century onwards. Its dating (6th-7th century) and size suggest that it was the original cathedral, possibly dating from the first mention of a bishopric in Elne in 571. The building, comprising a single nave completed by a semicircular apse, was in use throughout the early Middle Ages before being abandoned in the 10th century after part of the apse collapsed due to erosion of the cliffs. For almost two hundred years, scholars, historians, and archaeologists have been investigating the origins of the bishopric of Elne and the site of the cathedral that preceded the 11th-century Romanesque building that sits atop the ancient oppidum. This contribution outlines the major stages in this research and the contribution that this recent discovery has made to our knowledge of the spread of Christianity and the first churches in Roussillon. It also traces the major developments on the plateau des Garaffes and the changes in the episcopal group between the 6th and 17th centuries and the modern era, when the cemeteries were transferred outside the walls and the bishop moved to Perpignan.